Characteristics that focus the conception of traditional architecture in Tacna - Mendoza Cornejo, Marlene (2015)
This research was conducted in November 2014, in the period that includes the beginning of the second academic semester 2014-11. In this stage of training of our students in the academic area of ​​Architecture, Heritage and Criticism, teachers prepare the student to develop their capacity for analysis and deepen their knowledge that they will later apply in a different context within a specific reality. In this sense, the present research was presented as objective to identify the level of knowledge and analytical skills that students present the seventh level, who manage and develop concepts related to traditional architecture, identifying the main characteristics, to then apply the concepts when designing an architecture with contemporary characteristics. 40 students from the Design Workshop course of the VII cycle of the academic area of ​​Architecture and Design were part of the sample, which is one of the first courses of the advanced level of their academic training. The students in this cycle have developed 03 courses related to the research topic, such as Ancient Architecture, Architecture from the Middle Ages to Pre-Modernity and Peruvian Architecture. The results of the study allow us to verify that the students have the knowledge related to the characteristics of Traditional Architecture, demonstrating its conceptual application in a moderate percentage of them. The results of the study allow us to verify that the students have the knowledge related to the characteristics of Traditional Architecture, demonstrating its conceptual application in a moderate percentage of them. Finally, it was concluded that the students of the Design Workshop VII course of cycle VII have a moderate level of knowledge and application of the main characteristics of Traditional Architecture, two of them being the rooting of the land and the inhabitants, as well as the economy of materials and construction means, the most prevalent characteristics and application of contemporary architecture.